1991
DOI: 10.1111/j.1745-4573.1991.tb00457.x
|View full text |Cite
|
Sign up to set email alerts
|

FUNCTIONAL PROPERTIES OF BEEF AND BEEF BY‐PRODUCT PROTEIN FRACTIONS IN FRANKFURTER BATTERS1

Abstract: Protein fractions /high ionic strength soluble (HIS), low ionic strength soluble (LIS) and insoluble (IN)] and myosin percentage of beef skeletal tissues were varied in model system frankfirrter batter formulations by substitution of lung, heart and spleen to investigate changes in stability and textural properties. Percentage myosin and HIS proteins were positively correlated to reheat yield and apparent strain and stress at failure in the cooked batters. The quantity of U S proteins was negatively correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1995
1995
2005
2005

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
1
1
Order By: Relevance
“…2 and 3) indicates that within the range of the protein solubility obtained in the present study, these attributes are more likely to be affected by the state of denaturation of the extracted proteins during batter formation as reflected in sarcoplasmic protein solubility rather than the total amount of proteins extracted. The result of our study also differed from the outcome by Nuckles and Smith (1991) who found a positive correlation between high‐ionic strength and a negative correlation between low‐ionic strength meat proteins with apparent stress and strain at failure of cooked batter. However, they did not determine the shear stress and strain at failure by using torsion testing, and the soluble proteins were also determined by using a different method from ours.…”
Section: Resultscontrasting
confidence: 99%
“…2 and 3) indicates that within the range of the protein solubility obtained in the present study, these attributes are more likely to be affected by the state of denaturation of the extracted proteins during batter formation as reflected in sarcoplasmic protein solubility rather than the total amount of proteins extracted. The result of our study also differed from the outcome by Nuckles and Smith (1991) who found a positive correlation between high‐ionic strength and a negative correlation between low‐ionic strength meat proteins with apparent stress and strain at failure of cooked batter. However, they did not determine the shear stress and strain at failure by using torsion testing, and the soluble proteins were also determined by using a different method from ours.…”
Section: Resultscontrasting
confidence: 99%
“…Substituting LFTB for muscle meat in frankfurters resulted in less soluble myofibrillar protein; therefore, less protein interactions probably occurred, resulting in softer texture of the frankfurters. Likewise, the greater amount of low ionic strength soluble proteins from LFTT (He and Sebranek, 1996) may have softening effects on texture (Nuckles and Smith, 1991). The LFTB had a greater collagen content as well, which may soften the texture of these products (Ladwig et al, 1989a).…”
Section: Evaluation Of Frankfurters Made With Lfttmentioning
confidence: 99%